1983
DOI: 10.1111/j.1475-6803.1983.tb00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Impact of Option Trading on Underlying Securities

Abstract: This paper examines the short-term impact of option listing before and after the moratorium. There is no clear evidence that option trading has an effect on volatility or variability of shares traded daily. However, when the results are evaluated by year of trading, two significant trends can be identified. A trend toward decreased price volatility and increased variability in the number of shares traded daily is shown in the underlying security shortly after option trading begins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 1 publication
3
16
1
Order By: Relevance
“…Evidence that beta remains unchanged is also reported by Trennepohl and Dukes (1979) and Whiteside, Dukes and Dunne (1983), who used daily data to calculate returns. However, Whiteside et al go on to point out that when their results are evaluated on a year by year basis, there is a tendency for postlisting betas to become progressively smaller relative to their pre-listing counterparts.…”
Section: Previous Studiesmentioning
confidence: 50%
“…Evidence that beta remains unchanged is also reported by Trennepohl and Dukes (1979) and Whiteside, Dukes and Dunne (1983), who used daily data to calculate returns. However, Whiteside et al go on to point out that when their results are evaluated on a year by year basis, there is a tendency for postlisting betas to become progressively smaller relative to their pre-listing counterparts.…”
Section: Previous Studiesmentioning
confidence: 50%
“…Ho & Liu (1995) extend the analysis by examining the volatility of the volume, but find no significant changes. In contrast to Ho & Liu (1995), an earlier study by Whiteside, Dukes & Dunne (1983) found a significant increase in the volatility of volume. Whiteside et al (1983) results must be tempered by the older time period (1973)(1974)(1975)(1976)(1977)(1978)(1979), which may not be reflective of contemporary impacts, as evidence by changing impacts on price.…”
Section: Literature Reviewcontrasting
confidence: 39%
“…Later research by DeTemple & Jorian (1990) and St Pierre (1998) support Conrad's (1989) findings of decreased volatility and unchanged beta, while Haddad & Vorrheis (1991) find decreased volatility at the same time as significantly decreased beta. In an earlier paper, Whiteside, Dukes & Dunne (1983), find that, in the short-term, variance decreased subsequent to option introduction. Skinner (1989) uses a before/after ratio to determine the change in variance, and also concludes that variance has fallen.…”
Section: Literature Reviewmentioning
confidence: 99%
“…prediction error) using the conventional single factor capital asset pricing model (CAPM). This is an approach to total risk decomposition commonly used in the option listing literature (Bowe & Mazouz, 2004;Chaudhury & Elfakhani, 1995;Damodaran & Lim, 1991;Draper, Yadav, & Watt, 1992;Sahlströ m, 2001;Skinner, 1989;Whiteside, Dukes, & Dunne, 1983). 7 Second, in contrast to other studies in the derivatives listing literature, we also employ the Fama and French (1992) three-factor model (TFM) to distinguish between systematic and diversifiable risk.…”
Section: Introductionmentioning
confidence: 99%